Volumetric assessment of solid pulmonary nodules on ultralow-dose CT: a phantom study - Eberhard, Matthias; Stocker, Daniel; Milanese, Gianluca; Martini, Katharina; Nguyen-Kim, Thi Dan Linh; Wurnig, Moritz C.; Frauenfelder, Thomas; Baumueller, Stephan (Journal of Thoracic Disease, 2019)
Background: To reduce the radiation exposure from chest computed tomography (CT), ultralow-dose CT (ULDCT) protocols performed at sub-millisievert levels were previously tested for the evaluation of pulmonary nodules (PNs). The purpose of our study was to investigate the effect of ULDCT and iterative image reconstruction on volumetric measurements of solid PNs. Methods: CT datasets of an anthropomorphic chest phantom containing solid microspheres were obtained with a third-generation dual-source CT at standard dose, 1/8th, 1/20th and 1/70th of standard dose [CT volume dose index (CTDIvol): 0.03–2.03 mGy]. Semi-automated volumetric measurements were performed on CT datasets reconstructed with filtered back projection (FBP) and advanced modelled iterative reconstruction (ADMIRE), at strength level 3 and 5. Absolute percentage error (APE) evaluated measurement accuracy related to the effective volume. Scan repetition differences were evaluated using Bland-Altman analysis. Two-way analysis of variance (ANOVA) assessed influence of different scan parameters on APE. Proportional differences (PDs) tested the effect of dose settings and reconstruction algorithms on volumetric measurements, as compared to the standard protocol (standard dose-FBP). Results: Bland-Altman analysis revealed small mean interscan differences of APE with narrow limits of agreement (–0.1%±4.3% to –0.3%±3.8%). Dose settings (P